Whole genome sequencing of a multidrug-resistant Bacillus thuringiensis HM-311 obtained from the Radiation and Heavy metal-polluted soil. (June 2020) - Zuo, Wenlu; Li, Jingchen; Zheng, Jie; Zhang, Lei; Yang, Qi; Yu, Yadong; Zhang, Zhidong; Ding, Qingqing
Abstract: Objectives: Bacillus thuringiensis (BT) is distributed widely in the environment and utilised frequently for its highly specific toxins to target insect. However, BT is potentially pathogenic due to the high similarity between BT and Bacillus anthracis (BA). Meanwhile, there are reports that heavy metal pressure can promote the proliferation of antibiotic resistance in microorganisms through the co-selection of metal resistance genes (MRGs) and antibiotic resistance genes (ARGs). The aim of this work was revealed the MRGs and ARGs in a novel heavy metal tolerant and drug-resistant strain – B. thuringiensis HM-311, which was isolated from radiation and heavy metal-contaminated soil in Xinjiang (China). Methods: The genome of B. thuringiensis HM-311 was sequenced using a PacBio RS II platform and Illumina HiSeq 4000 platform at the Beijing Genomics Institute (BGI, Shenzhen, China). Results: The total size of B. thuringiensis HM-311 genome was 6, 019, 481 bp with a GC content of 35.85%. 134 genes related to antibiotics resistance and 75 genes related to heavy metal resistance were predicted in the B. thuringiensis HM-311 genome, the main ARGs and MRGs were discussed. Moreover, 30 verified virulence factor genes and 297 predicted virulence factor genes were annotated in the B. thuringiensis HM-311 genome. Conclusions: This genome can be used as a reference sequence for comparative genomic studies, elucidating antibiotic resistance development and the relationship between antibiotic resistance genes and heavy metal resistance genes in B. thuringiensis .